The Prevalence and Cause(s) of Burnout Among Applied Psychologists: A Systematic Review - McCormack, Hannah M.; MacIntyre, Tadhg E.; O'Shea, Deirdre; Herring, Matthew P.; Campbell, Mark J. (Frontiers in Psychology, 2018)
Purpose: Burnout has been shown to develop due to chronic stress or distress, which has negative implications for both physical and mental health and well-being. Burnout research originated in the “caring-professions.” However, there is a paucity of research which has focused specifically on how job demands, resources and personal characteristics affect burnout among practitioner psychologists. Methods: This PRISMA review (Moher, Liberati, Tetzlaff, Altman, & Group, 2009) involved searches of key databases (i.e. Web of Knowledge, SCOPUS, and Google Scholar) for articles published prior to 1st January 2017. Published articles concerning the prevalence and causes of burnout and stress in applied psychologists that were published in the English language were included. Both quantitative and qualitative investigative studies were included in the review. An inductive content analysis approach (Thomas, 2006) was subsequently conducted in order to identify the emerging themes from the data. Results: The systematic review comprised 29 studies. The most commonly cited dimension of burnout by applied psychologists was emotional exhaustion (34.48% of papers). Atheoretical approaches were common among the published articles on burnout among applied psychologists. Workload and work setting are the most common job demands and factors that contribute to burnout among applied psychologists, with the resources and personal characteristics of research are age and experience, and sex the most commonly focused upon within the literature. Conclusions: The results of the current study offer evidence that burnout is a concern for those working in the delivery of psychological interventions. We provide a critical summary of the measurement, incidence, resources, and characteristics of burnout in the mental health care profession. Finally, tentative recommendations for those within the field of applied psychology.